2021
DOI: 10.6007/ijarbss/v11-i5/9800
|View full text |Cite
|
Sign up to set email alerts
|

How to Curb up the HIV/AIDS Prevalence in Bangladesh?

Abstract: HIV/AIDS epidemic represents an emerging health threat for the whole World. HIV/AIDS occurrence rate In Bangladesh is still below 1percent but eventually is becoming a threat for the nation. However, the absence of sufficient research on HIV in the Bangladesh context motivates this secondary research. The present study discusses the strength, weaknesses, and interventions taken to combat HIV in Bangladesh. Also, it presents the key challenges that can potentially hinder progress in combating HIV. Finding demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…7 The highest at-risk groups for transmissibility of HIV/AIDS infection in Pakistan includes transsexuals, males, and women with a rate of 5.2%, 1.6%, and 0.6% respectively. 8 It showed that new models and modifications in injection, in particular, have been a critical factor contributing to a rapid increase in HIV amongst drug users. 9 According to the Pakistan Demographic and Health Survey, there are 490 and 84 cases of AIDS in Punjab, 395 and 43 cases of AIDS in KP, and 349 and 53 cases of AIDS in all four provinces combined.…”
Section: Introductionmentioning
confidence: 99%
“…7 The highest at-risk groups for transmissibility of HIV/AIDS infection in Pakistan includes transsexuals, males, and women with a rate of 5.2%, 1.6%, and 0.6% respectively. 8 It showed that new models and modifications in injection, in particular, have been a critical factor contributing to a rapid increase in HIV amongst drug users. 9 According to the Pakistan Demographic and Health Survey, there are 490 and 84 cases of AIDS in Punjab, 395 and 43 cases of AIDS in KP, and 349 and 53 cases of AIDS in all four provinces combined.…”
Section: Introductionmentioning
confidence: 99%